SISTEM INFORMASI PENJUALAN CAT BERBASIS MULTIUSER: (Studi Kasus CV KARUNIA ABADI Semarang) - Elsiana Tri Andri Antini; Ahmad Ashifuddin Aqham (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2024)
Growth of computer technology which is fast to progressively give amenities for human being in executing life activity, this matter result usage of computer is alternative taken by various institution because assessed more giving advantages compared to existing loss. Computer are appliance assist to improve performance various area. In finishing the problem of data processing in CV. Karunia Abadi, pursuant to execution of [done/conducted] survey, writer try to alter data-processing program by manual with computerization program.. This change aim gives freshment in the running of him. With computer program in data input still need time old ones and if for the seeking of data also still have to write one by one since it cannot by automatic and presentation which must be sent to leader still walk tardy so that cannot be presented anytime,because of this existence problem the writer try to formulate problems that is " How to make data-processing program of sale by cash and automatically can give report at any times at] leader in CV.Karunia Abadi using program of Microsoft Fox Pros 9.0". For data-processing process of sale can be accessed swiftly, and precisely and also give more drawing appearance. In finishing the problems [of] writer try to collect data - data which is connect with cash sale data. In scheme of system which is just [done/conducted] [by] some steps cover scheme of data. Making of tables, making of ERD. In data processing of the sale expected can assist problems of arising out in CV. Karunia Abadi. Endless Grant from above and made program it is of course still has some insuffiency and weakness, this matter is enabled [by] because still a few/little knowledge and experience of writer in problem of program. Suggestion and criticism very assist writer to be more develop knowledge in the field of this